2022
DOI: 10.5194/acp-22-2309-2022
|View full text |Cite
|
Sign up to set email alerts
|

Wet deposition in the remote western and central Mediterranean as a source of trace metals to surface seawater

Abstract: Abstract. This study reports the only recent characterization of two contrasted wet deposition events collected during the PEACETIME (ProcEss studies at the Air–sEa Interface after dust deposition in the MEditerranean Sea) cruise in the open Mediterranean Sea (Med Sea) and their impact on trace metal (TM) marine stocks. Rain samples were analysed for Al, 12 TMs (Co, Cd, Cr, Cu, Fe, Mn, Mo, Ni, Pb, Ti, V and Zn) and nutrient (N, P, dissolved organic carbon) concentrations. The first rain sample collected in the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 111 publications
6
8
0
Order By: Relevance
“…Concentrations of most TMs in rainwaters in our study, including Cd, Co, Cu, Mn, Ni, Pb and Zn, were similar to those reported for the central and western Mediterranean Sea (two individual samples), where wet deposition is influenced by high dust loading and anthropogenic emissions (Desboeufs et al., 2022). However, Fe concentrations were lower by a factor of ∼20 compared to the Mediterranean study (Desboeufs et al., 2022). The difference is perhaps related to the enhanced dust loadings in the Mediterranean Sea region, derived from the Sahara and Sahel areas (Baker et al., 2013; Nickovic et al., 2013; Sedwick et al., 2007) and/or low Fe concentrations of pyrogenic aerosol from South Africa (Barkley et al., 2019; Sholkovitz et al., 2012).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Concentrations of most TMs in rainwaters in our study, including Cd, Co, Cu, Mn, Ni, Pb and Zn, were similar to those reported for the central and western Mediterranean Sea (two individual samples), where wet deposition is influenced by high dust loading and anthropogenic emissions (Desboeufs et al., 2022). However, Fe concentrations were lower by a factor of ∼20 compared to the Mediterranean study (Desboeufs et al., 2022). The difference is perhaps related to the enhanced dust loadings in the Mediterranean Sea region, derived from the Sahara and Sahel areas (Baker et al., 2013; Nickovic et al., 2013; Sedwick et al., 2007) and/or low Fe concentrations of pyrogenic aerosol from South Africa (Barkley et al., 2019; Sholkovitz et al., 2012).…”
Section: Resultssupporting
confidence: 90%
“…The Congo shelf experienced numerous heavy rain events during our cruise, with precipitation rates of >1 mm hr −1 as confirmed by satellite data (Figure 1 and Figure S1 in Supporting Information ). We thus consider wet deposition as a potentially important source of TMs to surface waters as reported for other ocean regions (Desboeufs et al., 2022; Schlosser et al., 2014). As a result of the episodic and dispersed nature of rain events, it is challenging to decouple rain from river inputs of dTMs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(Yechieli & Wood, 2002). Atmospheric inputs are signi cant sources of trace metals, dissolved Fe, and Co in surface seawater (Desboeufs et al, 2022). The Carbon and nutrient inputs into soil and surface water are aided by atmospheric deposition (Mladenov et al, 2012;Qiao et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The Mediterranean Sea is subject to natural and anthropogenic exogenous chemical substances coming from rivers, effluents and atmospheric deposition (Guieu et al, 2002;Heimbürger et al, 2010Heimbürger et al, , 2011Pey et al, 2010;Llamas-Dios et al, 2021;Desboeufs et al, 2022). Important changes have been observed in recent decades in small pelagic fish populations of the northwestern Mediterranean Sea related to various environmental factors (Coll et al, 2019).…”
Section: Introductionmentioning
confidence: 99%